Classification of death causes after transplantation (CLASS): Evaluation of methodology and initial results. Issue 29 (July 2018) - Wareham, Neval Ete; Da Cunha-Bang, Caspar; Borges, Álvaro H.; Ekenberg, Christina; Gerstoft, Jan; Gustafsson, Finn; Hansen, Ditte; Heilmann, Carsten; Helleberg, Marie; Hillingsø, Jens; Krohn, Paul Suno; Lodding, Isabelle Paula; et al.
Abstract : Abstract: Correct classification of death causes is an important component of transplant trials. We aimed to develop and validate a system to classify causes of death in hematopoietic stem cell (HSCT) and solid organ (SOT) transplant recipients. Case record forms (CRF) of fatal cases were completed, including investigator-designated cause of death. Deaths occurring in 2010 to 2013 were used for derivation; and were validated by deaths occurring in 2013 to 2015. Underlying cause of death (referred to as recorded underlying cause) was determined through a central adjudication process involving 2 external reviewers, and subsequently compared with the Danish National Death Cause Registry. Three hundred eighty-eight recipients died 2010 to 2015 (196 [51%] SOT and 192 [49%] HSCT). The main recorded underlying causes of death among SOT and HSCT were classified as cancer (20%, 48%), graft rejection/failure/graft-versus-host-disease (35%, 28%), and infections (20%, 11%). Kappa between the investigator-designated and the recorded underlying cause of death was 0.74 (95% CI 0.69–0.80) in derivation and comparable in the validation cohort. Death causes were concordant with the Danish National Death Cause Registry in 37.2% (95% CI 31.5–42.9) and 38.4% (95% CI 28.8–48.0) in the derivation and validation cohorts, respectively. We developed and validated a method to systematically and reliably classify the underlying cause of death among transplant recipients. There was a high degree of discordance between this classification and that in the Danish National Death Cause Registry. Abstract : Supplemental Digital Content is available in the text